Digital Transformation of Mentawai Islands Tourism Through a User-Centered Website Using the Waterfall Method - Ora Pronobis Saogo; Ummul Khair (PT. Technology Laboratories Indonesia (TechnoLabs), 2026)
The rapid advancement of information technology has significantly accelerated digital transformation in the tourism sector by improving the accessibility and dissemination of tourism information. The Mentawai Islands possess considerable tourism potential, including marine tourism, natural attractions, and cultural heritage. However, the availability of integrated digital information remains limited, reducing the effectiveness of tourism promotion. This study aims to design and develop a web-based tourism information system for the Mentawai Islands using the Waterfall software development method with a focus on user-centered interface design. The research was conducted through five sequential phases: requirements analysis, system design, implementation, testing, and maintenance. The developed website provides comprehensive tourism information, including destination descriptions, tourism categories, image galleries, location maps, and contact information. Functional testing was performed using the Black Box Testing method to evaluate the performance of each system feature. The results indicate that the developed website successfully provides structured tourism information, enhances user experience through an intuitive interface, and improves the effectiveness of digital tourism promotion. Therefore, the proposed system can support the digital transformation of tourism management while increasing public accessibility to tourism information in the Mentawai Islands.